Penegakan Pidana Terhadap Pelaku Tindak Pidana Mucikari Melalui Media Online Di Wilayah Hukum Kepolisian Resor Kota Padang - Gema Dwi Arnepri; Sry Wahyuni (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2025)
Life in the current era of globalization is increasingly developing so that human life is made easier by rapid progress initheicurrent era of globalization, especially in the media, currently non-social media is not just television but there are many media that are increasingly developing day by day, especially in social media. As social media develops, the criminal crimes that occur today also increase, one of which is the crime of online prostitution, where prostitution is usually carried out online, but now prostitution can be carried out online, as is often heard now is that pimps carry out transactions through online media, apart from making it easier for the perpetrators of pimping, the media also makes it easier for the users of pimping services. The media that pimps usually carry out transactions through online media are WhatsApp, Twitter, Facebook, Instagram, Chat, and even via the web, Padang City is one of the cities where pimp prostitution cases have also been discovered through online media. The problem formulation in this research is 1). How is the enforcement of criminal law carried out by the Padang City Resort Police regarding criminal acts of pimping through online media in the jurisdiction of the Padang City ResortiPolice. 2). What are the obstacles experienced by the Padang City Police in carrying out criminal law against pimps via online media in the Padang City Resort Police Area? This research uses empirical juridical research, data is collected from interviews with the Padang City Police, the nature of the research is descriptive, and the data sources from this research are primary, secondary and tertiary legal materials. The results of the research are that the Police explain what punishments are, what forms of financial punishment are obstacles for the Police in enforcing the Criminal Law for perpetrators of the crime of pimping through online media.